Nagios Core Optimization by Utilizing Telegram as Notification of Disturbance - Fahreza Fahreza; Muhammad Rifqi (IJTI International Journal of Transportation and Infrastructure eISSN 2597-4769 pISSN 2597-4734)
Network Monitoring System (NMS) is a system that is highly demanded internet service provider industry in this fast-developing information technology era. The availability of NMS is the best option to restore the service level agreement as a means to compete with other internet service providers’ competitors. The occurrence of disturbance in the network is often unnoticed by the network administrator. This may lead to a crucial problem in decreasing network quality as the impact of time-consuming in solving the problem. Through the explanation, the writer tried to anticipate by classifying problems using Pareto, and integrated Nagios with Telegram Messenger as a notification of disturbance. Nagios has many features such as reports, event handler, monitoring resource (CPU load, memory usage, status up / down, up time, data traffic, bandwidth), etc. One of notable feature owned by Nagios is blast notification of disturbance. It is a feature that will function when one of the devices is in trouble. This feature will inform the network administrator or authorized person in a certain divisions as regards the error network. In this case, the problematic device can be categorized according to the parameters made by the network administrator.